Silver-Nanoparticle- and Silver-Nitrate-Induced Antioxidant Disbalance, Molecular Damage, and Histochemical Change on the Land Slug (Lehmannia nyctelia) Using Multibiomarkers - Bakr, Zeinab; Said, Shimaa Mohamed; Mohammad, Wafaa A.; Aboulnasr, Gehad N.; Elshimy, Naser A. (Frontiers in Physiology, 2022)
It is known that silver nanoparticles (Ag NPs) and AgNO3 have harmful effects on the surrounding organisms, which may cause damage to these organisms. Therefore, the aim of this study is to detect damage caused by Ag NPs and silver nitrate to land slugs (Lehmannia nyctelia). In this study, the slugs were exposed to various concentrations of Ag NPs and AgNO3 for 15 days. The biochemical, antioxidant, lipid peroxidation (LPO), DNA fragmentation, and histopathological endpoints were assessed after 15 days of exposure to different concentrations of Ag NPs (0.04, 0.08, 0.4, and 0.8 g/L) and silver nitrate (0.04, 0.08, 0.4, and 0.8 g/L). The results show a significant decrease in total protein, total carbohydrate, superoxide dismutase, and GST and a significant increase in total lipid, LPO, and DNA fragmentation after exposure to Ag NPs and AgNO3 for 15 days compared with the control group.